Les militantes anarchistes individualistes : des femmes libres à la Belle Époque - Anne Steiner (Amnis)
In the early years of the twentieth century, there were women who struggled for the right to free sexuality, spreading advice and methods for voluntary birth limitation; they thought about new methods of education, refused marriage and monogamy, and experimented with communal living. As individualist anarchist activists, they did not believe that revolution or insurrectional strikes could prevail in a near future and refused to be in the position of a sacrificed generation. In their view, individual emancipation was a preliminary condition for collective emancipation and struggle against prejudices was a matter of urgency, which is why they questioned all norms, customs and habits, wishing to obey reason only. These women, who were teachers, laundresses or servants, left few traces in history, and are largely forgotten today. In retracing their itineraries and their writings, this article aims at restoring their visibility to some extent.